Sudurnes Regional Heating Corporation: Svartsengi, Iceland - Thorolfsson, Geir (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2005)
The Svartsengi geothermal plant is a combined heat and power (CHP) plant. The heating plant supplies hot water to a district heating system (hitaveita) serving 20,000 people. The total installed capacity of the combined plants at Svartsengi is 46.4 MWe electrical power and 150 MJ/s (MWth) in the form of hot water. The Svartsengi geothermal area is close to the town of Grindavik on the Rekjanes peninsula and is part of an active fissure swarm, lined with crater-rows and open fissures and faults. The high-temperature area has an area of 2 sq km and shows only limited signs of geothermal activity at the surface